Harmony of religion and culture: fiqh munākahat perspective on the Gayo marriage custom - Dri Santoso; Wahyu Abdul Jafar; Muhamad Nasrudin; Musda Asmara; Fauzan Fauzan (State Institute of Islamic Studies (IAIN) Salatiga, 2022)
This study aimed to describe the established harmony between religion and culture within the traditional Gayo marriage custom. In addition, it determined whether the blending of religion and culture in traditional Gayo marriages adheres to fiqh munākahat. This study was descriptive and qualitative field research using the sociological juridical approach. Interviews and documentation were used as data collection methods. Meanwhile, to identify informants, researchers employed a purposive sampling technique. The important finding of this study was that in traditional Gayo marriages, religion and culture are harmonized appropriately and without coercion. The acculturation of fiqh munākahat evidences harmonization: ta'aruf (introduction), khitbah (proposal), marriage advice, discussions, i'lanu nikah (marriage announcement), and hospitality. The acculturation of the fiqh munākahat concept is found in the procession of the risik kono (introduction of the bride and groom's family), the munginte (proposal), the beguru (giving advice), the betelah (discussion), the segenap and begenap (discussion and family), the mah bai (accompanying the groom) and mah beru (accompanying the bride), mah kero opat ingi (carrying rice for four days) and tanag kul (a visit to the bride's house). Moreover, only two of the five Gayonese marriage customs adhere to the fiqh munākahat: ango/juelen (patrilineal) and kuso now (to and fro) marriages. In contrast, engagement marriages (matrilineal), Naik (eloping) and mah tabak (marriage submission) are not in line with fiqh munākahat.